A comparison of the seed dispersal service offered by chimpanzees (Pan troglodytes) and gorillas (Gorilla gorilla) - Bunney, Katherine (Department of Biological Sciences, 2017)
The handful of studies that have investigated chimpanzee and gorilla seed-dispersal identify these primates as important dispersal agents. These studies do not, however, make any measure of the 'quality' of the dispersal service offered by chimpanzees and gorillas. Determining 'quality' requires a measure of the dispersal distance and the microsite to which the seeds are dispersed. In this study, I report the first estimate of seed dispersal curves for chimpanzees and gorillas. Seed dispersal curves were produced by combining ape movement data with gut passage curves from literature. The derived dispersal distances for chimpanzees and gorillas are similar c. 7.7 km; this is surprisingly large when compared with other seed dispersal agents. This is likely due to a combination of foraging behaviour and gut physiology. At a species level, chimpanzees (Pan troglodytes) were shown to direct dispersal of Uapaca palidosa to favourable microsites even though gorillas (Gorilla gorilla) were responsible for moving a greater number of seeds. This study presents a novel method for the rapid derivation of dispersal curves and highlights the importance of incorporating species. level as well as community level studies to assess the quality of seed dispersal agents. It is my hope that the methods presented here be applied elsewhere so that the role of extant megaherbivores as seed dispersal agents be incorporated into future models that investigate forest dynamics.